Relevance Of Devidend Policy As The Mediation On The Relationship Between Financial Performance and Debt On Share Prices - Tyasari, Irma; Setiyowati, Supami Wahyu (JBMP (Jurnal Bisnis, Manajemen dan Perbankan), 2021)
The investors place great importance on the share price of publicly traded companies since it may reflect the company’s value. The research objective is to examine the relationship between financial performance and debt at share prices through dividend policy. The method of the research used is quantitative and correlational research. The data analysis technique is the use of smart PLS. The results of the study explain that financial performance has a positive effect on stock prices in the mediation of dividend policy. Debt negatively affects share price mediated by dividend policy. The implication of the study is that companies should consider the benefits as well as risks of borrowing funds from third parties. Investors and potential investors before investing their money in stocks must pay attention to financial performance, corporate debt and dividend policy so that they do not experience losses in their investment.